THE APPLICATION OF BUSINESS PROCESS MINING TO IMPROVING A PHYSICAL ASSET MANAGEMENT PROCESS: A CASE STUDY - Greyling, Berno Theo; Jooste, Wyhan (The South African Journal of Industrial Engineering, 2017)
Business process planning and control is important for effectively managing and improving processes relating to the management of physical assets. This is especially true when processes affect the uptime and value creation by physical assets. This article presents a case study where an asset management process is analysed using a technique called ‘process mining’, with which it is possible to investigate the process as it is being performed in the real world. By applying process mining instead of a traditional mathematical approach, real-world issues can be identified and corrected to improve the effectiveness of the given process. A process model is first constructed to investigate process execution patterns, after which dotted charts are used to identify problem areas within the process and to propose possible areas for improvement.